Role of financial, human and social capital in survival of start-ups - WONG, Tiong Kiat (Institutional Knowledge at Singapore Management University, 2019)
In new business ventures, growth in itself is often not the main intention in the beginning, but rather a mean to ensure survivability first, follow by sustainability and secure profitability. Not all small businesses survived over time and are always confronted with the liability of newness and contending externalities such as fierce competition and internal limitations like resources to survive. Only about half of newly founded start-ups survived after 5 years. The presence or absence of resources and the critical role it plays on the effect of venture’s survival, provides substantive advancement in understanding of organisational theory and management practice specifically on privately held small business. In this study, I will explore three types of resources: (i) financial capital, (ii) human capital, and (iii) social capital, and how they influence the survivability of start-ups. Longitudinal data on 36,969 privately held new ventures confirmed the differing influences of resources on survival. Using Cox proportional hazards model with time-dependent covariates, results show that both financial capital and human capital factors positively enhances survivability, and social capital factors having mixed direction of the relationship. While results show that social resources factor like board size and ethnic diversity alone indicate a negative relationship with survivability, further study suggest that if the board size increases to sufficiently large, ethnic diversity can positively moderate the relationship to enhance survivability, i.e. reversing the direction of the relationship. In this study, I further examine the moderating effect of financial capital on the human and social capital relationships with venture’s survival, results suggest that with the availability of slack resources, entrepreneurs are not effectively leveraging the strength of their founder’s human capital and social capital when deploying or utilising the resources, potentially undertaking more risky projects or sub-optimal decisions resulting in negative impact to performance.